Study on the prevalence and factors associated to vulvodynia in Spain. (September 2019) - Gómez, Isabel; Coronado, Pluvio J.; Martín, Clara M.; Alonso, Ruben; Guisasola-Campa, Francisco J.
Abstract: Objective: To study the prevalence and epidemiological characteristics of women with vulvodynia. To assess the risk factors associated to the disease. Study design: A cross-sectional study was made in which questionnaires were anonymously and confidentially distributed to Spanish women over 18 years of age between April 2016 and September 2017. The questionnaires were distributed by e-mail and through social networks, women's associations and specific websites. This type of questionnaire has been validated and used in many studies of this kind. The women answered questions referred to epidemiological aspects, demographic parameters, medical history, the presence of vulvodynia, associated factors, and comorbidities. Results: A total of 684 questionnaires were completed. The prevalence of vulvodynia was 6.6% (45 women). Thirteen percent (95 women) had experienced vulvodynia at some point in life. The factors associated to vulvodynia were prior vaginal deliveries (p = 0.001), vulvovaginal candidiasis (p < 0.001) and urinary tract infections (p < 0.001). Other pain syndromes such as fibromyalgia (p = 0.012), painful bladder syndrome/ interstitial syndrome (p < 0.001), temporomandibular joint pain (p = 0.021), coxofemoral pain (p = 0.001) or headache (p = 0.001) have also been associated to vulvodynia. Conclusions: The prevalence of vulvodynia in Spain is similar to that found in other countries. Many factors are involved in its development and persistence, particularly the presence of other pain syndromes and recurrent infections that could trigger complex inflammatory reactions.